Time Series Analysis of International Dollar Denominated Interest Rates - Finnerty, Joseph E.; Schneeweis, Thomas (Journal of International Business Studies, 1979)
The yield levels and yield movements of Eurodollar rates are compared to yield levels and yield movements of similar U.S. securities. Contrary to the previous studies, we could find no consistent and meaningful lead-lag relationship between U.S. rates and Eurodollar rates. Additionally, we found that long-term Eurodollar rates are not determined by long distributed lag of short-term rates. With and without capital controls and despite increased liquidity and more information there exist difference in yield levels and yield movements.